The Persepsi Guru Pendidikan Agama Islam tentang Technological Pedagogical Content Knowledge antara MTs Billingual Muslimat dan MTs al-Muawwanah - Hakka Ahmadia Mustawa; Munawir Munawir (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat Institut Agama Islam Syarifuddin Lumajang, 2021)
This research aims to analyze the perception of teachers in the 21st century in technological pedagogical content knowledge (TPACK). The method in this research is descriptive qualitative. Data collection techniques using observation instruments, interviews, and also surveys through the Googleform application. There were 12 informants in this study consisting of 6 Islamic teachers at MTs al-Muawwanah Sidoarjo and 6 Islamic teachers at MTs Billingual Muslimat NU Sidoarjo. The results of this study indicate that teachers who are in the school have perceptions with good categories in the use of the TPACK (Technological Pedagogical Content Knowledge) model. In this study also found that some of these teachers have problems in applying TPACK. The problem depends on the completeness of school facilities and infrastructure.